A Study to Assess Sociodemographic Profile and Prevalence of Metabolic Syndrome in Patients with Psychiatric Disorders - Dr. Vivek Pratap Singh; Dr. Archana Javadekar; Dr. Ekram Goyal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aim: The aim of the present study to assess sociodemographic profile and prevalence of metabolic syndrome in patients with psychiatric disorders. Methods: The cross-sectional study was conducted at Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune from July 2015 to September 2017 and 126 patients were included in the study. Results: The majority of patients 78 (61.9%) were in the age group of less than 40 years and there were 48(38.1%) cases who were aged more than 40 years. Majority of cases were females 67 (53.2%) and 59 (46.8%) cases were males. 47 (37.3%) patients were having metabolic syndrome as compared to 79 (62.7%) who were not having metabolic syndrome. 56 (44.4%) cases were having Schizophrenia, 3 (2.38%) were having Delusional disorder, 25 (19.8%) cases were from others group, 22 (17.5%) cases were from Bipolar Affective Disorder and Manic episode group. There was significant difference of age according to metabolic syndrome was found in the study group as p value was <0.0001. A significant association was found between sex and metabolic syndrome and the data showed that females were more prone to metabolic syndrome as compared to males. There was no statistical significant relation was found between disease type and metabolic syndrome. A significant relation was found between family history of psychiatric illness and metabolic syndrome as p value was found to be <0.05. Conclusion: The factors which were found to be responsible for high risk of metabolic syndrome in psychiatric disorders were older age, female gender, schizophrenia and family history of psychiatric illness.